Valve Replacement in Children with Single Ventricle Physiology - Alshami, Noor (Pediatr Cardiol, 2019)
Severe atrioventricular valve (AVV) or semilunar valve (SLV) regurgitation in the setting of a single ventricle physiology may proceed to valve replacement if repair strategies fail. Outcome data for these children are limited. We present transplant-free survival of a case series of children with single ventricle physiology undergoing either atrioventricular replacement (AVVR) or semilunar valve replacement (SLVR) from a multi-institutional, US-based registry (Pediatric Cardiac Care Consortium—PCCC). Outcomes were derived from PCCC and by linkage with the National Death Index (NDI) and Organ Procurement Transplant Network (OPTN). Fifty children with single ventricle physiology were identified to have received either AVVR (n = 38) or SLVR (n = 12). There were 17 in-hospital deaths including 8 intraoperative deaths (all intraoperative deaths were among children requiring AVVR). The in-hospital mortality was 42% and 8% for AVVR and SLVR, respectively. Among the 33 children surviving to hospital discharge, follow-up was available in 15 (46%). Death or cardiac transplant after hospital discharge occurred in 10—death in 4 (all among those requiring AVVR), cardiac transplant in 6 (2 following AVVR, 4 following SLVR). Valve replacement in children with single ventricle physiology, especially AVVR, is associated with poor outcomes. Alternative palliation strategies should be considered in children with single ventricle physiology with significant AVV or SLV regurgitations.